THE INFLUENCE OF FINANCIAL DISTRESS, DEBT COVENANT AND POLITICAL COST ON ACCOUNTING CONSERVATISM IN BANKING SECTOR FINANCIAL SERVICES COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Wulandari Cahyani Putri; Lindawati Lindawati; Syamsul Mu'arif (Asosiasi Dosen Muda Indonesia, 2023)
This research aims to prove empirically the effect of financial distress, debt covenants, and political costs on accounting conservatime. This research was conducted in a financial services company in the banking sector listed on the Indonesia Stock Exchange (IDX) in 2016–2020. The research method used is descriptive quantitative. The type of data used is secondary data. Samples were collected using purposive sampling method. The number of companies that were used as research samples were 22 companies with a research period of 5 (five) years, so that 110 samples were obtained. Data processing using Microsoft Office Excel Program and Statistics Program Eviews 9 analyzed descriptive statistics, model suitability test, classical assumption test, coefficient of determination (R2), panel data regression analysis, F statistical test and t statistical test. The results of the F statistical test for financial distress, debt covenants, and political costs variables simultaneously affect accounting conservatism. The results of the t-statistical test for the financial distress variable have a negative effect on accounting conservatism, debt covenants and political costs partially have a positive effect on accounting conservatism.